Relationship of Adolescent Women's Knowledge about Reproductive Health to Adolescent Pregnancy in Kelurahan Baru Ladang Bambu - Lubis, Suriati; Hasanah, Dwi Ris (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Adolescence comes from the Latin